FALSIFIKASI SEBAGAI PEDOMAN MEMAHAMI INFORMASI DI MEDIA SOSIAL SECARA OBJEKTIF - Putra, Yogi Irdes; Kusmana, Ade; Fitrah, Yundi (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2023)
Abstract This research aims to explain prevention efforts for social media users to avoid confirming information and the dangers of fake news. This research uses qualitative research methods and literature studies which are based on the philosophy of Karl R Popper's falsification theory. The results of this research found that Popper's ideas were ideas that really avoided the truth of something. Objective and rational assessments are carried out when reading information on social media by paying attention to the truth and the purpose of the information presented. The research recommendation is that all social media users think critically and rationally in responding to information in cyberspace. Keywords: Falsification; Information; Social Media; Objective.